A graphene-based conductive hydrogel and its preparation method and application

By combining graphene with polyvinyl alcohol and chitosan to form a dual network hydrogel, and using graphene quantum dot dispersion to form a conductive path, the problem of insufficient mechanical properties and conductivity of flexible wearable sensors is solved, and the problem of insufficient mechanical properties and conductivity of flexible wearable sensors is achieved High sensitivity and stability for multifunctional sensor applications.

CN115160602BActive Publication Date: 2024-12-13SUN YAT SEN UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202211009303.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-19
Publication Date
2024-12-13
Estimated Expiration
2042-08-19

AI Technical Summary

Technical Problem

Existing flexible wearable sensors have shortcomings in mechanical properties, conductivity and stability, making it difficult to achieve high sensitivity and versatility, especially poor dispersion of graphene in aqueous solution, resulting in poor conductivity.

Method used

Graphene is combined with polyvinyl alcohol and chitosan, and a dual network hydrogel is formed through cyclic freeze-thaw and sodium citrate soaking, which improves the dispersion and conductivity of graphene, and evaporates the solvent through the graphene quantum dot dispersion liquid to form graphite. ene powder, enhancing conductive pathways.

Benefits of technology

The prepared graphene-based conductive hydrogel has excellent mechanical properties, conductivity and flexibility. It is suitable for flexible wearable sensors and human-machine interfaces, and can sensitively detect human activities and maintain good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115160602B_ABST
    Figure CN115160602B_ABST
Patent Text Reader

Abstract

The invention discloses a graphene-based conductive hydrogel and a preparation method and application thereof, belonging to the field of biomaterial technology; the preparation method comprises the following steps: mixing graphene with a polyvinyl alcohol solution evenly to obtain a graphene-based polyvinyl alcohol mixed solution; adding chitosan to the graphene-based polyvinyl alcohol mixed solution and mixing evenly, then standing and hydrating to obtain a graphene-based polyvinyl alcohol chitosan mixed solution; freezing and thawing the graphene-based polyvinyl alcohol chitosan mixed solution and soaking it in a sodium citrate solution to obtain a graphene-based conductive hydrogel. The graphene-based conductive hydrogel provided by the invention has excellent mechanical properties, conductivity and flexibility; therefore, the graphene-based conductive hydrogel provided by the invention has broad application prospects in the fields of flexible wearable sensors, as well as human-machine interfaces, electronic skins and the like; and the preparation method provided by the invention is simple to operate and easy to use in actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomaterials, and in particular relates to a graphene-based conductive hydrogel and a preparation method and application thereof. Background Art

[0002] The wide application of wearable electronic devices in the fields of artificial skin, artificial intelligence, environmental monitoring and medical diagnosis has attracted more and more attention. Various sensors are key components of wearable electronic devices. Traditional sensors composed of rigid materials cannot be in close contact with human skin, making it difficult to achieve wearability and resulting in insufficient functionality. Therefore, flexible wearable sensors have attracted extensive research. Despite this, there are still some challenges in the practical application of flexible wearable sensors: the selection of flexible materials, simpler and more efficient preparation methods and device structures to improve the detection sensitivity, detection limit, linearity and stability during the process. Therefore, it is still a huge challenge to prepare flexible wearable sensors with high sensitivity, stable conductivity and multifunctionality.

[0003] Hydrogels are one of the most promising materials in the field of flexible wearable devices due to their high flexibility. Hydrogels are hydrophilic polymer networks containing a large amount of water synthesized by physical or chemical crosslinking. Due to their good flexibility, high water absorption and biocompatibility, hydrogels have been widely used in the fields of tissue engineering, biomedicine and smart devices. However, the wide application of hydrogels is limited by the lack of conductivity and sufficient mechanical properties. Conductive and mechanically strong hydrogels are an emerging class of hydrogels that have been widely studied by researchers due to their excellent flexibility, biocompatibility, ductility and similarity to biological tissue structures. Conductive hydrogels can be prepared by compounding with conductive fillers or combining ionic side groups or salts. The synthesized conductive hydrogels combine the electronic properties of conductive materials and the flexibility of hydrogels, thus attracting widespread attention in the application of wearable devices. In recent years, a large number of flexible strain sensors based on conductive hydrogels have been prepared. However, it is still a challenge to obtain conductive hydrogels with high strength, high sensitivity and flexibility for wearable strain sensors.

[0004] Polyvinyl alcohol (PVA) is a commonly used material for synthesizing polymer hydrogels. It has excellent properties such as low toxicity, biocompatibility, high hydrophilicity, easier film-forming ability, chemical resistance and mechanical resistance. There are many reports on PVA hydrogel sensors, but there are few sensors that have flexibility, excellent mechanical properties and stability. Graphene is a sp 2Hybrid connected carbon atoms are tightly stacked into a new material with a single-layer two-dimensional honeycomb lattice structure, which has high mechanical strength and good electrical conductivity. Graphene oxide is prepared by harsh oxidative exfoliation of graphite. After oxidation, the number of oxygen-containing functional groups on the surface of graphene oxide increases, making its properties more active than graphene, and it can be well dispersed in aqueous solution. According to relevant literature reports, graphene has poor dispersibility in aqueous solution. Graphene oxide and reduced graphene oxide are usually used as conductive fillers and composited with polymers to prepare conductive hydrogels. However, due to the defects in its molecular structure, graphene oxide exhibits poor conductivity. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a graphene-based conductive hydrogel with good mechanical properties, conductivity and flexibility, and a preparation method and application thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a graphene-based conductive hydrogel, the preparation method comprising the following steps:

[0007] (1) mixing graphene and polyvinyl alcohol solution uniformly to obtain a graphene-based polyvinyl alcohol mixed solution;

[0008] (2) adding chitosan to the graphene-based polyvinyl alcohol mixed solution of step (1) and mixing them evenly, and then standing them for hydration to obtain a graphene-based polyvinyl alcohol chitosan mixed solution;

[0009] (3) freeze-thaw the graphene-based polyvinyl alcohol chitosan mixed solution described in step (2), and then soak it in a sodium citrate solution to obtain a graphene-based conductive hydrogel.

[0010] In a method for preparing a graphene-based conductive hydrogel provided by the present invention, a highly soluble short-chain chitosan (CS) is mixed with a polyvinyl alcohol (PVA) solution, and after cyclic freeze-thaw and sodium citrate soaking treatment, a double network hydrogel is formed by ionic crystallization cross-linking, so that it has excellent mechanical properties; the conductive circuit formed by the graphene compound in the double network hydrogel gives the hydrogel good conductivity. Specifically, the chitosan used in the present invention is an abundant natural product with biodegradability, biocompatibility, and antibacterial effects. Introducing chitosan into polyvinyl alcohol hydrogel to form a composite hydrogel can overcome the limitations of a single polyvinyl alcohol hydrogel; adding chitosan after mixing graphene with a polyvinyl alcohol solution can enhance the dispersibility of graphene and improve the conductivity of the product.

[0011] As a preferred embodiment of the preparation method of the present invention, in the graphene-based polyvinyl alcohol chitosan mixed solution, the mass percentage of graphene is 0.05-0.85%, the mass percentage of polyvinyl alcohol is 6-12%, and the mass percentage of chitosan is 3-7%.

[0012] As a preferred embodiment of the preparation method of the present invention, in the graphene-based polyvinyl alcohol chitosan mixed solution, the mass percentage of graphene is 0.45%, the mass percentage of polyvinyl alcohol is 10%, and the mass percentage of chitosan is 5%.

[0013] The inventors have found that when the mass percentage of polyvinyl alcohol is 6-12% and the mass percentage of chitosan is 3-7%, especially when the mass percentage of polyvinyl alcohol is 10% and the mass percentage of chitosan is 5%, the mechanical properties of the obtained graphene-based conductive hydrogel are better; when the mass percentage of graphene is 0.05-0.85%, especially when the mass percentage of graphene is 0.45%, the conductivity of the obtained graphene-based conductive hydrogel is better; if the mass percentage of graphene is further increased, the excess graphene will be stacked in the double network, which will reduce the conductivity of the hydrogel.

[0014] As a preferred embodiment of the preparation method of the present invention, the preparation method of the polyvinyl alcohol solution is: dissolving polyvinyl alcohol in boiling deionized water by stirring, and obtaining the polyvinyl alcohol solution after the polyvinyl alcohol is completely dissolved.

[0015] As a preferred embodiment of the preparation method of the present invention, the graphene is graphene powder, and the preparation method thereof is: evaporating the solvent in the graphene quantum dot dispersion to obtain the graphene powder.

[0016] The inventors have found that ordinary graphene has poor dispersibility in aqueous solution, so it is not conducive to compounding in hydrogel to form a conductive path; by replacing ordinary graphene with graphene powder formed by evaporating the solvent of graphene quantum dot dispersion as raw material, the problem of poor dispersibility in aqueous solution can be well overcome, and finally the product can achieve good conductivity.

[0017] As a preferred embodiment of the preparation method of the present invention, in step (3), the freeze-thaw process is first freezing at (-28) to (-20)°C for 3 to 6 hours, and then thawing at room temperature for 3 to 6 hours.

[0018] As a preferred embodiment of the preparation method of the present invention, the method further comprises centrifuging the graphene-based polyvinyl alcohol chitosan mixed solution to remove bubbles before freeze-thawing.

[0019] As a preferred embodiment of the preparation method of the present invention, in the step (2), the standing hydration time is 12 to 24 hours.

[0020] As a preferred embodiment of the preparation method of the present invention, the concentration of the sodium citrate solution is 1.3 mol / L.

[0021] In addition, the present invention also provides a graphene-based conductive hydrogel, and the graphene-based conductive hydrogel is prepared by the preparation method of the present invention.

[0022] In addition, the present invention also provides an application of the graphene-based conductive hydrogel in the fields of flexible wearable strain sensors, human-machine interfaces, and electronic skin.

[0023] The graphene-based conductive hydrogel provided by the present invention has excellent mechanical properties, conductivity and flexibility, and the polyvinyl alcohol and chitosan used in the raw materials have good biocompatibility; the problem of mismatch between tissues and devices can be solved. The hydrogel of the present invention is applied to a flexible wearable strain sensor, which can sensitively detect human activities, such as finger bending, wrist bending, elbow bending, knee bending, etc., and the prepared sensor has good stability and durability; therefore, the graphene-based conductive hydrogel prepared by the present invention has broad application prospects in the field of flexible wearable sensors, as well as human-machine interfaces, electronic skins and other fields.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The graphene-based conductive hydrogel provided by the present invention forms a double-network hydrogel by forming polyvinyl alcohol and chitosan in an appropriate mass percentage range and having good biocompatibility, and adds a certain amount of graphene powder formed by evaporating the solvent of a graphene quantum dot dispersion into the double-network hydrogel, thereby forming a conductive path in the double network, so that the prepared graphene-based conductive hydrogel has excellent mechanical properties, conductivity and flexibility at the same time; therefore, the graphene-based conductive hydrogel provided by the present invention has broad application prospects in the field of flexible wearable sensors, as well as human-machine interfaces, electronic skins and other fields; and the preparation method provided by the present invention is simple to operate and easy to use in actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the preparation process of graphene-based conductive hydrogel in Example 3;

[0027] Figure 2 This is the mechanical properties diagram of the PVA / CS hydrogel tested in Effect Example 1;

[0028] Figure 3 This is the conductive performance test diagram in effect example 2;

[0029] Figure 4 This is a comparison chart of mechanical properties in effect example 3;

[0030] Figure 5 This is a diagram showing the test results of human finger bending motion in Effect Example 4;

[0031] Figure 6 This is a graph showing the cyclic tensile test results in Effect Example 5. DETAILED DESCRIPTION

[0032] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0033] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0034] Example 1

[0035] The present invention provides a series of PVA / CS hydrogels with different mass percentages of polyvinyl alcohol, and the specific preparation method is as follows:

[0036] 3g, 4g, 5g, and 6g of polyvinyl alcohol were dissolved in 44.5mL, 43.5mL, 42.5mL, and 41.5mL of deionized water, respectively, and stirred at 300rpm at 100°C until completely dissolved, and then cooled to room temperature to obtain a polyvinyl alcohol solution; then 2.5g of chitosan was added to the polyvinyl alcohol solution and stirred at 300rpm until it became uniform and translucent, and then placed at room temperature for 12h until fully hydrated; then the fully hydrated product was placed in a centrifuge at a speed of 5000r / min for 1h to remove bubbles and then loaded into a mold, the mold was placed at (-26)°C and frozen for 4h, then taken out and thawed at room temperature for 4h; finally, the thawed product was placed in a 1.3mol / L sodium citrate solution and soaked for 1.5h to obtain PVA / CS hydrogels with a mass percentage of polyvinyl alcohol of 6%, 8%, 10%, and 12%, respectively.

[0037] Example 2

[0038] The present invention provides a series of PVA / CS hydrogels with different mass percentages of chitosan, and the specific preparation method is as follows:

[0039] 2.5g of polyvinyl alcohol was dissolved in 21.8mL, 21.5mL, 21.3mL, 21mL, and 20.8mL of deionized water, respectively, and stirred at 300rpm at 100°C until completely dissolved, and then cooled to room temperature to obtain a polyvinyl alcohol solution; then 0.75g, 1g, 1.25g, 1.5g, and 1.75g ​​of chitosan were added to the polyvinyl alcohol solution, and stirred at 300rpm until it became uniform and translucent, and then placed at room temperature for 12h until fully hydrated; then the fully hydrated product was placed in a centrifuge at a speed of 5000r / min for 1h to remove bubbles and then loaded into a mold, the mold was placed at (-26)°C and frozen for 4h, then taken out and thawed at room temperature for 4h; finally, the thawed product was placed in a 1.3mol / L sodium citrate solution and soaked for 1.5h to obtain PVA / CS hydrogels with chitosan mass percentages of 3%, 4%, 5%, 6%, and 7%, respectively.

[0040] Example 3

[0041] The present invention provides a graphene-based conductive hydrogel. The schematic diagram of the preparation process of the graphene-based conductive hydrogel is as follows: Figure 1 As shown, the specific preparation method is as follows:

[0042] (1) Preparation of graphene powder: evaporating the solvent in the graphene quantum dot dispersion to obtain graphene powder;

[0043] (2) Preparation of polyvinyl alcohol solution: 5 g of polyvinyl alcohol was dissolved in 42.5 mL of deionized water, and the mixture was stirred at 100° C. and 300 rpm until the mixture was completely dissolved to obtain a polyvinyl alcohol solution;

[0044] (3) adding 0.025 g of graphene powder to the polyvinyl alcohol solution and stirring at 300 rpm for 1 h until the mixture is uniformly mixed to obtain a graphene-based polyvinyl alcohol mixed solution;

[0045] (3) After the graphene-based polyvinyl alcohol mixture is cooled to room temperature, 2.5 g of chitosan is added, and the mixture is stirred at a speed of 300 rpm until it becomes uniform and translucent, and then placed at room temperature for 12 hours until it is fully hydrated; then the fully hydrated product is placed in a centrifuge at a speed of 5000 r / min for 1 hour to remove bubbles and then loaded into a mold, and the mold is placed at (-26) ° C and frozen for 4 hours, then taken out and thawed at room temperature for 4 hours; finally, the thawed product is placed in a 1.3 mol / L sodium citrate solution and soaked for 1.5 hours to obtain a graphene-based conductive hydrogel with a mass percentage of graphene of 0.05%.

[0046] Example 4

[0047] The embodiment of the present invention provides a graphene-based conductive hydrogel, and the specific preparation method is as follows:

[0048] (1) Preparation of graphene powder: evaporating the solvent in the graphene quantum dot dispersion to obtain graphene powder;

[0049] (2) Preparation of polyvinyl alcohol solution: 5 g of polyvinyl alcohol was dissolved in 42.4 mL of deionized water, and the mixture was stirred at 100° C. and 300 rpm until the mixture was completely dissolved to obtain a polyvinyl alcohol solution;

[0050] (3) adding 0.125 g of graphene powder to the polyvinyl alcohol solution and stirring at 300 rpm for 1 h until the mixture is uniformly mixed to obtain a graphene-based polyvinyl alcohol mixed solution;

[0051] (3) After the graphene-based polyvinyl alcohol mixture is cooled to room temperature, 2.5 g of chitosan is added, and the mixture is stirred at a speed of 300 rpm until it becomes uniform and translucent, and then placed at room temperature for 12 hours until it is fully hydrated; then the fully hydrated product is placed in a centrifuge at a speed of 5000 r / min for 1 hour to remove bubbles and then loaded into a mold, and the mold is placed at (-26) ° C and frozen for 4 hours, then taken out and thawed at room temperature for 4 hours; finally, the thawed product is placed in a 1.3 mol / L sodium citrate solution and soaked for 1.5 hours to obtain a graphene-based conductive hydrogel with a mass percentage of graphene of 0.25%.

[0052] Example 5

[0053] The embodiment of the present invention provides a graphene-based conductive hydrogel, and the specific preparation method is as follows:

[0054] (1) Preparation of graphene powder: evaporating the solvent in the graphene quantum dot dispersion to obtain graphene powder;

[0055] (2) Preparation of polyvinyl alcohol solution: 5 g of polyvinyl alcohol was dissolved in 42.3 mL of deionized water, and the mixture was stirred at 100° C. and 300 rpm until the mixture was completely dissolved to obtain a polyvinyl alcohol solution;

[0056] (3) adding 0.225 g of graphene powder to the polyvinyl alcohol solution and stirring at 300 rpm for 1 h until the mixture is uniformly mixed to obtain a graphene-based polyvinyl alcohol mixed solution;

[0057] (3) After the graphene-based polyvinyl alcohol mixture is cooled to room temperature, 2.5 g of chitosan is added, and the mixture is stirred at a speed of 300 rpm until it becomes uniform and translucent, and then placed at room temperature for 12 hours until it is fully hydrated; the fully hydrated product is then placed in a centrifuge at a speed of 5000 r / min for 1 hour to remove bubbles and then loaded into a mold, and the mold is placed at (-26) ° C and frozen for 4 hours, then taken out and thawed at room temperature for 4 hours; finally, the thawed product is placed in a 1.3 mol / L sodium citrate solution and soaked for 1.5 hours to obtain a graphene-based conductive hydrogel with a mass percentage of graphene of 0.45%.

[0058] Example 6

[0059] The embodiment of the present invention provides a graphene-based conductive hydrogel, and the specific preparation method is as follows:

[0060] (1) Preparation of graphene powder: evaporating the solvent in the graphene quantum dot dispersion to obtain graphene powder;

[0061] (2) Preparation of polyvinyl alcohol solution: 5 g of polyvinyl alcohol was dissolved in 42.2 mL of deionized water, and stirred at 100° C. and 300 rpm until completely dissolved to obtain a polyvinyl alcohol solution;

[0062] (3) adding 0.325 g of graphene powder to the polyvinyl alcohol solution and stirring at 300 rpm for 1 h until the mixture is uniformly mixed to obtain a graphene-based polyvinyl alcohol mixed solution;

[0063] (3) After the graphene-based polyvinyl alcohol mixture is cooled to room temperature, 2.5 g of chitosan is added and stirred at a speed of 300 rpm until it becomes uniform and translucent, and then placed at room temperature for 12 hours until it is fully hydrated; then the fully hydrated product is placed in a centrifuge at a speed of 5000 r / min for 1 hour to remove bubbles and then loaded into a mold, and the mold is placed at (-26) ° C and frozen for 4 hours, then taken out and thawed at room temperature for 4 hours; finally, the thawed product is placed in a 1.3 mol / L sodium citrate solution and soaked for 1.5 hours to obtain a graphene-based conductive hydrogel with a mass percentage of graphene of 0.65%.

[0064] Example 7

[0065] The embodiment of the present invention provides a graphene-based conductive hydrogel, and the specific preparation method is as follows:

[0066] (1) Preparation of graphene powder: evaporating the solvent in the graphene quantum dot dispersion to obtain graphene powder;

[0067] (2) Preparation of polyvinyl alcohol solution: 5 g of polyvinyl alcohol was dissolved in 42.1 mL of deionized water, and the mixture was stirred at 100° C. and 300 rpm until the mixture was completely dissolved to obtain a polyvinyl alcohol solution;

[0068] (3) adding 0.425 g of graphene powder to the polyvinyl alcohol solution and stirring at 300 rpm for 1 h until the mixture is uniformly mixed to obtain a graphene-based polyvinyl alcohol mixed solution;

[0069] (3) After the graphene-based polyvinyl alcohol mixture is cooled to room temperature, 2.5 g of chitosan is added and stirred at a speed of 300 rpm until it becomes uniform and translucent, and then placed at room temperature for 12 hours until it is fully hydrated; then the fully hydrated product is placed in a centrifuge at a speed of 5000 r / min for 1 hour to remove bubbles and then loaded into a mold, and the mold is placed at (-26) ° C and frozen for 4 hours, then taken out and thawed at room temperature for 4 hours; finally, the thawed product is placed in a 1.3 mol / L sodium citrate solution and soaked for 1.5 hours to obtain a graphene-based conductive hydrogel with a mass percentage of graphene of 0.85%.

[0070] Effect Example 1

[0071] Effect Example 1 of the present invention verifies the mechanical properties of the PVA / CS hydrogels with different mass percentages of polyvinyl alcohol in Example 1 and the PVA / CS hydrogels with different mass percentages of chitosan in Example 2; specifically, the prepared PVA / CS hydrogel is pressed into a tensile specimen with a length of 12 mm and a width of 2 mm on a tablet press and placed in a universal stretching machine to test its mechanical properties. Before the test, the thickness of the tensile specimen is measured and recorded; the stretching rate is 10 mm / min, and the test temperature is room temperature. The test results of the PVA / CS hydrogels with different mass percentages of polyvinyl alcohol in Example 1 are as follows: Figure 2 As shown in (a), the test results of PVA / CS hydrogels with different mass percentages of chitosan in Example 2 are as follows Figure 2 (b). Figure 2 As can be seen from (a), as the mass percentage of polyvinyl alcohol gradually increases, the mechanical properties of the obtained hydrogel show a trend of first increasing and then decreasing. Among them, when the mass percentage of polyvinyl alcohol is 10%, the obtained PVA / CS hydrogel has the best mechanical properties. Figure 2 As can be seen in (b), the mass percentage of chitosan has a significant impact on the mechanical properties of the hydrogel. When the mass percentage of chitosan is 5%, the obtained PVA / CS hydrogel has the best mechanical properties.

[0072] Effect Example 2

[0073] Effect Example 2 of the present invention verifies the conductive properties of the graphene-based conductive hydrogel prepared in Examples 3-7. Specifically, the graphene-based conductive hydrogel prepared in Examples 3-7 is cut into rectangular parallelepiped strips with similar specifications, and the length, width and thickness are measured and recorded. Then, the resistance is measured by connecting with a wire, and each strip is tested three times to obtain the average value. The experimental results are as follows: Figure 3 As shown. Figure 3 It can be seen that with the increase of the mass percentage of graphene, the conductivity of the obtained graphene-based conductive hydrogel first increases and then decreases. When the mass percentage of graphene is 0.45%, the obtained graphene conductive hydrogel has the highest conductivity.

[0074] Effect Example 3

[0075] Effect Example 3 of the Invention The mechanical properties of the graphene-based conductive hydrogel prepared in Example 5 and the PVA / CS hydrogel in Example 1 when the mass percentage of polyvinyl alcohol is 10% are compared. Specifically, the prepared product is pressed into a tensile specimen with a length of 12 mm and a width of 2 mm on a tablet press and placed on a universal stretching machine to test its mechanical properties. The thickness of the tensile specimen is measured and recorded before the test; the stretching rate is 10 mm / min, and the test temperature is room temperature. The results are as follows: Figure 4 As shown, (a) represents PVA / CS hydrogel, (b) represents graphene-based conductive hydrogel; Figure 4 As can be seen in (a), PVA / CS hydrogel has good mechanical properties, with a fracture stress of 0.85Mpa and an elongation of 165%. Compared with PVA / CS hydrogel, graphene conductive hydrogel has higher fracture stress and elongation, with a fracture stress of 1.58Mpa and an elongation of 185%. This is because the graphene conductive filler is compounded in the PVA / CS hydrogel double network, which can also further enhance the mechanical properties of the hydrogel.

[0076] Effect Example 4

[0077] Effect Example 4 of the present invention The graphene-based conductive hydrogel prepared in Example 5 is assembled into a flexible sensor for detecting the bending movement of human fingers, which specifically includes the following steps: The graphene-based conductive hydrogel prepared in Example 5 is assembled into a flexible sensing device using a wire, copper tape and VHB tape and placed on a human finger, and the corresponding resistance change of the finger in the bent and straight relaxed state is measured, such as Figure 5As shown, (a) represents a finger bending 30°, (b) represents a finger bending 60°, and (c) represents a finger bending 90°; it can be seen from the figure that when the finger is bent, the hydrogel is stretched, resulting in an increase in resistance, and the resistance returns to the original value when the finger contracts. The resistance of the hydrogel-based sensor changes regularly and stably, indicating that the response behavior of the prepared graphene-based conductive hydrogel is stable and repeatable. In addition, when the finger is bent at different angles of 30°, 60°, and 90°, the change in resistance is different. The larger the bending angle, the greater the change in resistance; indicating that the sensor sensitively detects the bending changes of the finger and has good sensing response characteristics.

[0078] Effect Example 5

[0079] Effect Example 5 of the Invention The graphene-based conductive hydrogel prepared in Example 5 was subjected to a cyclic tensile test, which specifically includes the following steps: The graphene-based conductive hydrogel prepared in Example 5 was assembled into a flexible sensing device using a wire, a copper tape and a VHB tape and placed on a stretching machine to measure the resistance change of the hydrogel during the tensile and compression cycle test, as shown in FIG. Figure 6 As shown. The graphene-based conductive hydrogel exhibits excellent strain sensing stability in tensile and compression cycle tests. Figure 6 It can be observed that the resistance change increases slightly with the increase in the number of cycles, which may be due to the slight elongation of the sample after the cyclic stretching. At the same time, the accumulation of small changes in the hydrogel network structure caused by mechanical stress with the increase in the number of cycles may cause small changes in the sensing signal. Nevertheless, after 500 stretching cycles, the change in hydrogel resistance still maintains a similar value, indicating that the sensor has excellent stability and repeatability.

[0080] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a graphene-based conductive hydrogel, characterized in that: The preparation method comprises the following steps: (1) mixing graphene and polyvinyl alcohol solution uniformly to obtain a graphene-based polyvinyl alcohol mixed solution; (2) adding chitosan to the graphene-based polyvinyl alcohol mixed solution of step (1) and mixing them evenly, and then standing them for hydration to obtain a graphene-based polyvinyl alcohol chitosan mixed solution; (3) freezing and thawing the graphene-based polyvinyl alcohol chitosan mixed solution in step (2), and then immersing the mixture in a sodium citrate solution to obtain a graphene-based conductive hydrogel; In the graphene-based polyvinyl alcohol chitosan mixed solution, the mass percentage of graphene is 0.05-0.85%, the mass percentage of polyvinyl alcohol is 6-12%, and the mass percentage of chitosan is 3-7%; The graphene is graphene powder, and the preparation method thereof is: evaporating the solvent in the graphene quantum dot dispersion to obtain the graphene powder with a particle size of 80-600nm.

2. The preparation method according to claim 1, characterized in that: In the graphene-based polyvinyl alcohol-chitosan mixed solution, the mass percentage of graphene is 0.45%, the mass percentage of polyvinyl alcohol is 10%, and the mass percentage of chitosan is 5%.

3. The preparation method according to claim 1, characterized in that: The preparation method of the polyvinyl alcohol solution is: stirring and dissolving polyvinyl alcohol in boiling deionized water, and obtaining the polyvinyl alcohol solution after the polyvinyl alcohol is completely dissolved.

4. The preparation method according to claim 1, characterized in that: In step (3), the freeze-thaw process is to first freeze at (-28) ~ (-20) ° C for 3 ~ 6 hours, and then thaw at room temperature for 3 ~ 6 hours.

5. The preparation method according to claim 1, characterized in that: In the step (2), the standing hydration time is 12 to 24 hours.

6. The preparation method according to claim 1, characterized in that: The concentration of the sodium citrate solution is 1.3 mol / L.

7. A graphene-based conductive hydrogel, characterized in that: The graphene-based conductive hydrogel is prepared by the preparation method according to any one of claims 1 to 6.

8. Application of the graphene-based conductive hydrogel as claimed in claim 7 in the fields of flexible wearable strain sensors, human-machine interfaces, and electronic skin.

Citation Information

Cited By

  • Super-strong, super-tough and all-weather anti-fatigue-fracture conductive hydrogel as well as preparation method and application thereof

    CN117986701A

  • Super-strong, super-tough and all-weather fatigue fracture resistant conductive hydrogel and preparation method and use thereof

    CN117986701B